EFFECT OF NANO ZINC OXIDE ON THE LEAF PHYSICAL AND NUTRITIONAL QUALITY OF SPINACH - B. KISAN; N. K. SHRUTHI; A. H. SHARANAGOUD; S. B. REVANAPPA; R. RAMACHANDRA; A. C. HOSAMANI; A. N. BHEEMANN; PRAMOD (The Bioscan, 2015)
Spinach (Spinaciaoleracea) belongs to familyAmaranthaceaeand is one of the important and nutritious leafy vegetable consumed in India. It has been postulated that Nano particles have the effect on germination growth at vegetative stage. Hence, the study was designed to test the ability of zinc Nano particles on the leaf physical and nutritional status of spinach. The spinach plants were sprayed with graded concentration of zinc oxide Nano particles (ZnO NPs) (0, 100, 500, 1000 ppm) after 14 days of sowing. The leaf physical parameters like leaf length, leaf width and leaf surface area, are recorded at the time of maturity (45-50 days), protein, carbohydrate, fat and dietary fiber content in leaf samples are determined. The plants sprayed with ZnO NPs at the concentration of 500 and 1000 ppm in comparison with control the increase over control was % leaf length (6.25 and 5.48), %protein (91.86 and 151.30), %fat (960 and 1470) and%fiber (69.15 and 242.82). Hence our study suggests that 1000ppm of Nano Zinc application will enhance the nutritive value of spinach to vegetarian diet by providing protein, fiber and required amount of vegetarian fat.